Analysis of Design Schemes of HMCVT - Zhu Zhen; Gao Xiang; Cao Leilei; Pan Daoyuan; Zhu Yu (Jixie chuandong, 2015)
Hydro- mechanical continuously variable transmission is a kind of power- split stepless transmission device,which realizes the stepless speed regulation by hydraulic regulating speed mechanism and the higher efficient by mechanical variable speed mechanism. The five simple and reliable stepless transmission device is designed autonomously,through the different combinations of hydraulic regulating speed mechanism and mechanical variable speed mechanism,the switch of hydraulic transmission,hydro- mechanical transmission and mechanical transmission is carried out to meet the requirements of smooth start,field operation and transportation,the power performance and fuel economy performance of diesel engine are given full play,and the transmission performance and efficiency of transmission are improved greatly. In order to reach the goal of energy conservation and emissions reduction,a simple introduction of energy storage device is given.